(102 - х)*96=6048
102 - х = 6 048 : 96
102 - х = 63
х = 102 - 63
х = 39
____________________
(102 - 39 ) * 96 = 6 048
6 048 = 6 048
211+х*72=5179
х * 72 = 5 179 - 211
х * 72 = 4 968
х = 4 968 : 72
х = 69
______________
211 + 69 * 72 = 5 179
5 179 = 5 179
234+26-х=96
260 - х = 96
х = 260 - 96
х = 164
____________
234 + 26 - 164 = 96
96 = 96
68*(х-68) = 6324
х - 68 = 6 324 : 68
х - 68 = 93
х = 93 + 68
х = 161
_____________
68 * ( 161 - 68 ) = 6 324
6 324 = 6 324
(2*х+48):16=6
2 * х + 48 = 6 * 16
2 * х + 48 = 96
2 * х = 96 - 48
2 * х = 48
х = 48 : 2
х = 24
____________
(2 * 24 + 48) : 16 = 6
6 = 6